Tindak Tutur Ekspresif dalam Komentar Youtube kanal Nihongo Mantappu episode “AKHIRNYA LULUS KULIAH! WISUDA WASEDA UNIVERSITY” - Ananda, Nadya Tri; Asnawi, Asnawi (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
A study on expressive speech acts in YouTube channel comments can provide valuable insights into various aspects of online interactions, such as community formation, negotiation of meaning, and expression of identity. The objective of this study is to describe the different forms and functions of expressive speech acts in the comments section of the YouTube video entitled